On the Autocorrelation of Growth Rates: Evidence for Micro, Small and Large Firms from the Austrian Service Industries, 1975-2004 - Alex Coad; Werner Hölzl (Austrian Institute of Economic Research (WIFO), 2008)
This paper studies the serial autocorrelation of annual growth rates in employment for selected Austrian service industries over a 30-year period using quantile regression techniques. The autocorrelation of growth rates provides important information on firms growth processes. We find that the growth patterns of micro firms are strikingly different from the growth patterns of small, medium-sized and larger firms. First, we do find a positive dependency of growth on size for growing micro firms, while this relationship is negative for the other size groups. Second, growing micro firms are subject to negative autocorrelation of annual growth rates making sustained growth a very rate occurrence, while larger growing firms usually display a positive autocorrelation suggesting that high growth episodes of larger firms stretch over a longer time horizon. This indicates that non-convex adjustment costs leading to lumpy growth are much more important for micro firms than for large firms. Furthermore, we find that the autocorrelation patterns are asymmetric with regard to decline and growth.
Keywords: 330; serial correlation; firm growth; service sector; quantile regression; Austria; Unternehmenserfolg; KMU; Großunternehmen; Dienstleistungssektor; Korrelation; Schätzung; Österreich